1994
DOI: 10.1111/j.1432-1033.1994.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution Electron Microscopic Studies on the Quaternary Structure of Ornithine Aminotransferase from Pig Kidney

Abstract: The ornithine aminotransferase (OAT) from pig kidney has been studied on the basis of highresolution electron microscopy and the morphological appearance of the apoenzyme and holoenzyme have been examined. The quaternary structure of the OAT molecules in the presence of 5 mM pyridoxal 5'-phosphate could be established. The enzyme molecule appears to be built up of two morphological units, called M1. The native holoenzyme, termed morphological unit M2, measures . 10.9 nm in length and 5.8 nm in width and its mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Moreover, we demonstrated that both holo and apo exist in solution as a tetramer. Although these data confirm previous analyses on mammalian OATs purified from different sources [13–16], they are in contrast with crystallographic analyses indicating the hexameric assembly of the enzyme [1821]. It is possible that the crystallization conditions, known to increase the solute concentration over that expected for an ideal solution, could promote the hexamerization.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, we demonstrated that both holo and apo exist in solution as a tetramer. Although these data confirm previous analyses on mammalian OATs purified from different sources [13–16], they are in contrast with crystallographic analyses indicating the hexameric assembly of the enzyme [1821]. It is possible that the crystallization conditions, known to increase the solute concentration over that expected for an ideal solution, could promote the hexamerization.…”
Section: Discussionsupporting
confidence: 83%
“…In fact ultracentrifugation and SEC studies on the OAT purified from rat and human liver [13–15] indicated that the enzyme has a tetrameric assembly. Accordingly, high resolution electron microscopy studies on OAT purified from pig kidney indicated that the holoenzyme is a homotetramer [16]. Moreover, Sanada et al have reported that the apo-OAT exists in dimeric form [14] raising a question about the possible role of the PLP in the OAT oligomerization.…”
Section: Introductionmentioning
confidence: 99%
“…Testing the consistency between the proteome profiles of both PRLTS3 patient fibroblast cultures (in triplicates) versus ClpP-null MEFs, we also noted significant accumulations of eleven mitochondrial matrix proteins ( Figure 4 C), which are not known as interactors of ClpX or ClpB: OAT, ASS1, ACADVL, STOM, PRDX3, PC, MUT, ALDH2, PMPCB, UQCRC2, and ACADSB, see Table 2 . Importantly, all of them are known for their assembly into homo-multimers or heterodimers [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. OAT, PC, ALDH2, PMPCB, and ACADSB also showed significant accumulation in ClpP-null brains ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not possible to tell from the crystal structure whether the hexamer is of biological relevance or merely an effect of crystal packing, there is experimental evidence for the existence of hexamers of rat liver OAT in solution approaching crystallization conditions [61]. Assemblies of dimers or tetramers have been observed in electron microscopic studies on pig kidney OAT [62], and oligomers are detected in high concentrations of mouse liver OAT [63]. The oligomerization state seems to change the kinetic properties of the enzyme [30], and may partly explain the differences observed between tissues, although the kinetic studies performed up till now have never shown any sign of cooperation between the various subunits (the kinetics seems to be of the Michaelis Menton type, see above).…”
Section: Structure Of Oatmentioning
confidence: 99%